2014
DOI: 10.18632/oncotarget.2123
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signaling sensitizes Glioma stem cells to endogenous nano-irradiation

Abstract: The existence of therapy resistant glioma stem cells is responsible for the high recurrence rate and incurability of glioblastomas. The Hedgehog pathway activity plays an essential role for self-renewal capacity and survival of glioma stem cells. We examined the potential of the Sonic hedgehog ligand for sensitizing of glioma stem cells to endogenous nano-irradiation. We demonstrate that the Sonic hedgehog ligand preferentially and efficiently activats glioma stem cells to enter the radiation sensitive G2/M ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Theoretically, expression of every gene in this network may have an influence on the overall functioning of the signaling pathway. Alterations in the expression profiles of many different genes can, therefore, lead to a similar result of a pathway activation or suppression during cancer development [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Theoretically, expression of every gene in this network may have an influence on the overall functioning of the signaling pathway. Alterations in the expression profiles of many different genes can, therefore, lead to a similar result of a pathway activation or suppression during cancer development [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, SMO , GLI1 , PTCH1 , CD133 and aldehyde dehydrogenase (ALDH)-expressing GSCs are upregulated post-radiation in GBM neurospheres, which further supports the concept that standard therapies are not able to abolish GSCs [ 115 ]. Additionally, it has been shown that active Hh signaling can sensitize GSCs to endogenous nano-irradiation, through the inhibition of thymidine synthesis [ 117 ].…”
Section: Evidence For the Role Of Hedgehog Signaling In Cancer Stementioning
confidence: 99%
“…The hedgehog signaling pathway has a vital role in the control of cell differentiation, cell proliferation and embryonic development ( 5 , 7 , 12 ). According to recent studies, aberrant activation of hedgehog signaling is linked to the aggressiveness of multiple tumor types, including GBM ( 21 , 22 ). The results of the present study are therefore consistent with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%